(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
Aim. Confirmation of the efficacy and safety of the drug riamilovir (Triazavirin®), 100 mg capsules, in children aged 12–17 years with the diagnosis of acute viral respiratory infection (ARVI).Materials and methods. The multicenter study included 269 patients diagnosed with acute viral respiratory infection (ICD-10 code: J00, J02, J02.9, J04, J04.0, J04.1, J04.2, J06, J06.0, J06.9) in the presence of clinical manifestations and confirmation of the etiology of the disease by laboratory tests (PCR method). Patients were included in the study after one of the patient’s parents/adoptive parents and the patient signed an informed consent to participate in the study. The interval between the appearance of the first symptoms of the disease and the inclusion of the patient in the study did not exceed 36 hours.Results. As a result of a clinical study, the efficacy and safety of treatment with riamilovir (Triazavirin®) in sick children aged 12–17 years with a diagnosis of ARVI was shown. A decrease in the duration of the disease was shown when using the drug riamilovir (Triazavirin®) compared with the control group. No serious adverse events were detected during the study.Conclusion. As a result of the conducted clinical study, the high efficacy, safety and good tolerability of the drug riamilovir in the treatment of children aged 12–17 years with a diagnosis of ARVI was established. It is recommended to use the drug riamilovir in clinical practice as an etiotropic therapy in children aged 12–17 years with a diagnosis of ARVI due to its high efficacy and safety.